INFLUENCE OF AN EXTERNAL TANK ON AERODYNAMIC CHARACTERISTICS OF CRYOPLAN - Y. S. Mikhailov; A. V. Petrov; V. I. Chernousov; V. V. Gubsky (Научный вестник МГТУ ГА, 2016)
The calculation and experimental investigations of an external fuel tank influence on longitudinal and lateral aerodynamic characteristics of the light transport cryoplan model has been executed. Tank influence on drag coefficient and lift-drag ratio of the model is presented. It's revealed the essential decreasing the model directional stability due to tank installation. Technical solutions intended for increasing cryoplan's directional stability are developed and preliminarily investigated.